Serum Lutein and Zeaxanthin Are Inversely Associated with High-Sensitivity C-Reactive Protein in Non-Smokers: The Mikkabi Study - Mieko Nakamura; Minoru Sugiura (MDPI AG, 2022)
Recent randomized controlled trials have demonstrated a protective association between carotenoids and inflammation; however, the basis of this association on lifestyle factors remains unclear. This study aimed to clarify the associations between carotenoids and inflammatory markers stratified by lifestyle factors, using baseline data from the Mikkabi Study. Serum carotenoid and high-sensitivity C-reactive protein (hs-CRP) levels were measured. Multivariable adjusted odds ratios (ORs) for a high hs-CRP level (≥2.0 mg/dL) were obtained using logistic regression analysis. The data of 882 individuals were analyzed; 11.7% had high hs-CRP levels. The highest tertile of lutein (OR: 0.44; 95% confidence interval [CI]: 0.25-0.76), zeaxanthin (OR: 0.36; 95% CI: 0.21-0.64), total carotenoid (OR: 0.57; 95% CI: 0.32-0.9997), and oxygenated carotenoid concentration (OR: 0.50; 95% CI: 0.28-0.90), with the lowest tertile as reference, was inversely associated with a high hs-CRP level. The interaction between lutein, but not other carotenoids, and current smoking was significant. The inverse association between lutein and a high hs-CRP level was significant in non-smokers (OR: 0.41; 95% CI: 0.22-0.76) but not in smokers. These results further support the anti-inflammatory effect of carotenoids; nevertheless, further studies should clarify the interaction of smoking with the association between lutein and inflammation.